Finite element modelling of structural clay brick masonry subjected to axial compression - Bakhteri, Jahangir; Makhtar, Ahmad Mahir; Sambasivam, Shamala (Penerbit UTM Press, 2004)

(untitled)
This Paper Presents The Numerical Verifications Of The Experimental Investigation On The Effect Of Mortar Joint Thickness On Compressive Strength Characteristics Of Axially Loaded Brick-Mortar Prisms. The Three Dimensional Micro Modeling Of The Prisms Was Based On Two Approaches: Firstly, Models Were Assumed To Be Made Of Homogeneous Material; The Second Approach Envisaged The Models As Composite Material Made Of Brick And Mortar. The Later Modeling Approach, Which Assumed The Prism To Be Made Of Composite Material, Gave More Accurate Prediction Of The Stress Distribution In The Prisms, And Also The Failure Loads Predictions Were In Good Agreement With The Experimental Results, Suggesting That This Modeling Approach With Composite Material Assumption Is More Appropriate Than The Homogenous Material Assumption. In The Present Work, A Strength Magnification Factor Has Also Been Proposed For The Design Purposes, Which Can Be Used To Assess The Experimental Compressive Strength Of The Brick Masonry From Its Finite Element Analysis Results.